Strategi Pengembangan Instalasi Rawat Inap Pada Rumah Sakit Hermina Pasteur - Andriani, Neneng Yanti (Balitbangda Provinsi Jambi, 2023)
This study aims to identify and analyze inpatient installation development strategies in an effort to improve service quality (Case Study at Hermina Pasteur Hospital).The results of this study are expected to contribute to increasing the ability of practitioners with regard to operational management studies and can provide input for solving problems in matters relating to management